Volammetric determination of butylated hydroxyanisol in biodiesel, mineral and synthetic oils using gold electrode - Tomášková, Markéta; Chýlková, Jaromíra; Jehlička, Vladimír; Navrátil, Tomáš; Šelešovská, Renáta (University of Pardubice, 2013)
Voltammetric determination of butylated hydroxyanisol (BHA) antioxidant in propan-2-ol containing 0.1 mol l–1 H2SO4 using DC voltammetry with gold working electrode was tested. The developed method is designed for determination of BHA in biodiesel, mineral, and synthetic oils. There were compared the results obtained by nonlinear and linear regression of recorded data. The program OKnelin was applied in evaluation by nonlinear regression. This method was applied to analysis of real model samples. Analyses in biodiesels can be performed directly, without necessity of sample pretreatment or extraction. The extraction is necessary for analyses in oils.